Zapleti pri pacientih po težki obliki COVID-19 - Cunder, Katarina (Rehabilitacija (Ljubljana), 2021)
Background: Before release of this paper, 65 patients after severe COVID-19 disease had been accepted for rehabilitation at the Department for rehabilitation of patients after trauma, with peripheral nerve injury and rheumatic disease of the University Rehabilitation Institute in Ljubljana, Slovenia. Methods: Based on documentation of patients that concluded rehabilitation between November 2020 and March 2021, we coded acute and subacute complications based on the International Classification of Diseases (ICD). Descriptive statistics were calculated. Results: The most common acute complications were secondary pneumonia, pressure wound, adrenal insufficiency, thromboembolic events and electrolyte disbalance. During rehabilitation the most common documented complications were urinary tract infection, ulnar and peroneal nerve palsy, an episode of mental disorder and hypokalemia. Conclusion: During acute treatment and during rehabilitation the patients included in this study suffered from complications arising from different organic systems. A complex approach of an extended rehabilitation team was therefore needed.
Keywords: acute complications; akutni zaplet; COVID-19; rehabilitacija; Rehabilitation; subacute complications; subakutni zaplet